Дослідження впливу використання натуральних і штучних оболонок на мікробіологічну стабільність і вологовміст варених ковбасних виробів у процесі зберігання - Пасічний, Василь Миколайович; Маринін, Андрій Іванович; Желуденко, Юлія Володимирівна; Задкова, Світлана Петрівна (My University, 2018)
У статті проведено порівняльний аналіз шляхів подовження термінів зберігання ковбасних виробів вареної групи. Визначено фонові показники мікробіологічного забруднення натуральних і штучних білкових та целюлозних оболонок, які вказують на більш високі значення МАФАнМ натуральних оболонок. Показано динаміку зміни вмісту вологи в сосисках вищого сорту в процесі зберігання залежно від виду використаних оболонок і проведено їх порівняння. Встановлено, що вплив на фізико-хімічний стан зразка практично мінімальний, однак більша відповідність технологічних показників є між натуральною і штучною білковою оболонками. За результатами досліджень можна зробити висновок, що використання штучних білкових оболонок, які за технологічними властивостями максимально наближені до натуральних, є перспективним напрямком подовження термінів зберігання варених ковбасних виробів. The article presents a comparative analysis of ways to extend of cooked sausages shelf life. Initial microbiological contamination of natural and artificial protein and cellulose casings have been determinant, which indicate higher values natural casings QMAFAnM. The dynamics of changes in the content of moisture in the highest grade cooked sausages during storage, depending on the type of used casing, is shown and their comparison is given. Sample physicochemical condition effect is found to be minimal, however, a greater correspondence of the technological parameters is between the natural and artificial protein casing. It is defined that for sausages in a natural casing on the sixth day of storage in traditional conditions for commercial networks at a temperature of 0+6°С and relative humidity of 75—78%, the possible accumulation of QMAFAnM is 7,5 • 102—1,3 • 103 CFU/g, which exceeds the standard values for cooked sausages. Sausages in the protein casing without the use of additional technological methods do not exceed the microbiological contamination standard values on the sixth day of storage. It is confirmed that cooked sausage using natural and artificial casing effect on the population of molds and yeasts are stable at storage time, with the keeping the production technology all samples showed stable meaning during storage time at all control points It is certain that the presence of coliforms, pathogenic flora, including Salmonella, sulfite-reducing clostridia, Listeria monocytogenes, Staphylococcus aureus for all types of sausages, does not depend on the type of casings used in the production. Based on the research results, it can be concluded that the use of artificial protein casings, which are as close to natural as possible by their technological properties, is a promising direction for extending the cooked sausages shelf life.
Keywords: ковбасні оболонки; сосиски; мікробіологічне забруднення; терміни зберігання; casings; sausage; microbial contamination; shelf life; кафедра технології м’яса і м’ясних продуктів; кафедра технологічного обладнання та комп’ютерних технологій проектування